Pendidikan Life Skills Dalam Sitem Pendidikan Pondok Pesantren Di Pesantren Mamba’ul Hikmah Wonoboyo Temanggung - Wadhifatul Asfiyak (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Life skill education is not only applied in public schools, but in islamic boarding schools also apply life skill education in everyday life. Especially in social skill education, with the aim that students can apply it in community life. This study uses a descriptive qualitatife research method. Data collection techniques include interviews, observations, and documentation. This study aims to determine the implementation of the social skill education system at the Mamba’ul Hikmah Wonoboyo Temanggung Islamic Boarding School. Student are equipped with social skill education both in the dormitory or outside the dormitory, namely classroom learning or extracurricural activities and organizations. Supporting factors in students’ social skill education are in the form of students’ discipline in carrying out activities. The inhibiting factor is juvenile delinquency.